2013
DOI: 10.6061/clinics/2013(12)12
|View full text |Cite
|
Sign up to set email alerts
|

Local and remote ischemic preconditioning protect against intestinal ischemic/reperfusion injury after supraceliac aortic clamping

Abstract: OBJECTIVES:This study tests the hypothesis that local or remote ischemic preconditioning may protect the intestinal mucosa against ischemia and reperfusion injuries resulting from temporary supraceliac aortic clamping.METHODS:Twenty-eight Wistar rats were divided into four groups: the sham surgery group, the supraceliac aortic occlusion group, the local ischemic preconditioning prior to supraceliac aortic occlusion group, and the remote ischemic preconditioning prior to supraceliac aortic occlusion group. Tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 40 publications
(41 reference statements)
0
17
0
1
Order By: Relevance
“…) and gut ischaemia (Erling et al . ), and in sepsis‐induced organ damage (Olguner et al . ) and it has been suggested that this technique might be used for additional non‐ischaemic bowl disorders.…”
Section: Hypoxia‐inducible Factors (Hifs)mentioning
confidence: 99%
See 1 more Smart Citation
“…) and gut ischaemia (Erling et al . ), and in sepsis‐induced organ damage (Olguner et al . ) and it has been suggested that this technique might be used for additional non‐ischaemic bowl disorders.…”
Section: Hypoxia‐inducible Factors (Hifs)mentioning
confidence: 99%
“…Additional animal studies indicate that RIP might be useful in other medical fields. Animal studies showed that RIP may also be organ protective in hepatic (Tapuria et al 2012) and gut ischaemia (Erling et al 2013), and in sepsis-induced organ damage (Olguner et al 2013) and it has been suggested that this technique might be used for additional non-ischaemic bowl disorders. The use of RIP in trauma may also improve the outcome of casualties, enhancing pre-hospital and overall survival.…”
Section: Additional Potential Clinical Uses For Ripmentioning
confidence: 99%
“…1,2 Mesenteric ischemia may occur owing to a restriction of intra-abdominal blood supply as a result of physiological conditions (e.g. exercise, stress) or in pathophysiological events such as strangulation, adhesions, thrombosis, embolies, trauma, shock, complications to surgery or organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the comparison between two independent groups, ALO-ALO and Fk-Fk-IPC, significance was observed (p = 0.035) to the beneficial effect of IPC-R in terms of development score. The role of IPC in reducing ischemic injury has been widely documented in a range of tissues, including IR injury of the small intestine [11][12][13][14][15][16] . A recent study shows that Ischemic preconditioning increased the intestinal stem cell activities in the intestinal crypts in mice 17 .…”
Section: Resultsmentioning
confidence: 99%